Adverse effects of confusion between forest species on sustainable management: the example of African mahoganies (Khaya, Meliaceae) - (:unkn) unknown (My University, 2019)
Species of the genus Khaya produce some of Africa’s most valuable timber. For two centuries, these species have all been traded as “African mahogany”. On the African continent, four different but morphologically similar species are now recognised: Khaya anthotheca, K. grandifoliola, K. ivorensis and K. senegalensis. The number of taxa included in the genus Khaya has varied over time, and the way these taxa are distinguished has implications for the development of sustainable management strategies for the different species. The aim of the study described in this article was to make sure that these species are distinguished on the basis of up-to-date knowledge on taxonomy, genetics, ecology and chemotaxonomy. Although the data available do not always suffice to clearly distinguish between the four mahogany species on the African continent, they do indicate that K. ivorensis, K. grandifoliola and K. senegalensis are probably distinct species whose taxonomic limits are yet to be clearly defined. It also seems that Khaya nyasica should be distinguished from K. anthotheca. Several chemotypes have been identified in the latter, suggesting that it could in fact cover a more complex group including at least two other taxa whose rank as species or sub-species is yet to be determined. Morphometric, genetic and ecological studies need to be developed to clarify the systemic status and evolutionary history of these different taxa, in order to formulate appropriate recommendations for the sustainable management of African mahoganies.
Keywords: African Research